A Picture of Abanded Children in Padang, A Human Interest Radio Feature - Hadi Permana; Sumira Sumira; Dhini Aulia (Politeknik Negeri Padang, 2018)
Abandoned children is one of the problems faced by Padang city. Many reasons make the number of abanded children still high. Although, the news about abandoned children have been posted in newspaper, magazine even online and social media, but seen that they just inform in partially. Therefore the researchers conducted a project on presenting the data on the picture of abanded children in padang in form of radio feature. It is expected that this radio feature can give useful information about the reason why they “work on the street”, the life that they run everyday. Hence it is hope that it can touch the human care of people and government to find the best solution for them. The data was gotten from the result of interview by using recorder tools. Then Cool Edit Pro 2.1 application was used to edit and mix the voice . Moreover this project applied the stages of making radio feature likes pre-production, production and post-production. The result of thisl project were in form of audio, radio feature with 15 minutes duration, and the English script with 756 word.